Climate Education in Kindergarten - Anna Klim-Klimaszewska; Sabina Wieruszewska-Duraj (Ignatianum University Press, 2023)
Climate change is one of the biggest challenges of our times, as it affects the way societies and economies around the world operate: from dangerous weather anomalies, through a drop in crop production, to an escalation of international conflicts. Moreover, the consequences of climate change pose a risk to many areas of life. Therefore, actions ought to be taken to limit it. For these actions to be effective, climate change education must start as early as kindergarten. The subject of the research presented in the article is the implementation of climate education in kindergartens in the Masovian Voivodeship, Poland. The objective of the study is to determine the level of knowledge among six-year-old children about climate, climate change, the related risks, actions that can be taken to prevent climate change, and whether and how the children's teachers cover topics related to climate change. The study consisted of diagnosing children's knowledge about climate and climate change and verifying preschool teachers' class register records and monthly work plans regarding climate change education. The analysis regarding children's awareness of climate and climate change demonstrates that they could not support their knowledge with concrete examples. It indicates a superficial environmental education targeted at the adoption of positive attitudes towards nature among children. The study reveals that despite some preschool teachers introducing climate education to their classes, in the majority of classrooms, climate-related issues are rarely discussed. The research demonstrates that preschool teachers are unaware of the fact that the present generation of preschool children will have an impact on the future of our planet. Therefore, it should be recommended that teachers promote the principles of sustainable development and foster an awareness of the effect of human activity on our environment and climate change.